Fine dried noodles containing tea polyphenol self-assembled nano aggregate and preparation method of fine dried noodles
By using the self-assembly of tea polyphenols in green tea noodles, a stable nano-aggregation is formed, which solves the problem of easy oxidation of tea polyphenols and difficulty in improving taste, and achieves high nutritional value and low-cost storage effects.
Patent Information
- Application Number
- CN202411901911.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-14
AI Technical Summary
While the existing green tea noodles improve the taste and nutritional value, it is difficult to effectively utilize tea polyphenols, and tea polyphenols are easy to oxidize, resulting in high product storage and transportation costs.
By utilizing the self-assembly of polyphenols in green tea, stable self-assembly nano-aggregation of tea polyphenols is formed, reducing dependence on other nutrients, and improving the stability and taste of tea polyphenols.
It has achieved the improvement of the taste and nutritional value of green tea noodles without adding other nutrients, delayed the oxidation process of tea polyphenols, and reduced product storage and transportation costs.
Smart Images

Figure BDA0005203418590000091 
Figure BDA0005203418590000092 
Figure BDA0005203418590000111
Abstract
Description
Technical Field
[0001] The present invention relates to the general technical field of food preparation, and in particular to dried noodles containing tea polyphenol self-assembled nano-aggregates and a preparation method thereof. Background Art
[0002] With the diversification of noodle products, there are more and more solutions to add substances to noodles to improve their taste and nutritional value.
[0003] For example, patent application number CN108936281A discloses a green tea noodle recipe. This recipe incorporates fungus, Chinese yam, carrot, Chinese herbal medicine powder, and green tea powder. This recipe not only imparts the unique fragrance and nutritional value of green tea, but also boasts the health benefits of lowering blood sugar, making it suitable for diabetics. Existing green tea noodle patents utilize both the tea flavor and tea polyphenols, which have antioxidant, anti-inflammatory, antibacterial, and lipid metabolism-regulating properties, imparting nutritional benefits to the noodles.
[0004] However, existing patents often rely on the addition of various nutrients to mask the bitterness and other side effects of green tea. This approach limits the amount of green tea added to meet desired noodle textures, ultimately resulting in both the desired taste and the nutritional benefits of green tea falling short of expectations. Furthermore, existing patents lack the ability to slow the oxidation of tea polyphenols. Therefore, in existing technologies, noodles rich in tea polyphenols often require low-temperature storage to prevent their inactivation, leading to high storage and transportation costs. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide noodles containing self-assembled nano-aggregates of tea polyphenols. The noodles of the present invention fully utilize the beneficial effects of the self-assembly phenomenon of polyphenols in green tea on the quality of the noodles. The self-assembly phenomenon of polyphenols refers to the phenomenon in which polyphenols undergo polymerization in an aerobic environment, under the catalytic action of metal ions, or under alkaline conditions. When the self-assembly phenomenon occurs in natural polyphenols, their phenolic hydroxyl groups can react with various substances (such as proteins, polysaccharides, and metal ions) under alkaline conditions to construct a variety of different phenolic network structures to form nano-aggregates. Such structures form colloidal particles on the micron or nanometer scale. These particles have a certain degree of stability and can impart the unique taste, aroma, and color of their carrier. Therefore, the present invention can reduce dependence on other expensive nutrients, increase the amount of green tea added, and reduce the occurrence of tea polyphenol oxidation in the finished noodles through the self-assembly phenomenon of tea polyphenols, greatly improving the taste and nutritional quality of the noodles.
[0006] The present invention is achieved through the following technical solutions:
[0007] The invention discloses noodles containing self-assembled nano-aggregates of tea polyphenols. The components required for preparing the noodles include, by weight, 85-110 parts of flour, 0.1-0.5 parts of soda ash, 1-2.5 parts of salt, 2-3.5 parts of konjac gum, and 30-60 parts of tea soup. The tea soup is obtained by brewing yellow green tea and water, and the mass ratio of the yellow green tea to the water in the tea soup is 1:(40-80).
[0008] As a further improvement of the present invention, the components required for preparing the noodles preferably include, by weight: 90-110 parts of flour, 0.1-0.3 parts of soda ash, 1.5-2.5 parts of salt, 2.5-3.5 parts of konjac gum, and 30-50 parts of tea soup; wherein the tea soup is obtained by brewing yellow green tea and water, and in the tea soup, the mass ratio of the yellow green tea to the water is 1:(60-80).
[0009] As a further improvement of the present invention, the optimal steaming time of the noodles is 200 to 300 seconds.
[0010] As a further improvement of the present invention, after the noodles are steamed within the optimal steaming time, the polyphenol content of the noodles is 20-25 mg / kg.
[0011] As a further improvement of the present invention, after the noodles are steamed within the optimal steaming time, the water absorption rate of the noodles is 125-150%.
[0012] As a further improvement of the present invention, after the noodles are steamed within the optimal steaming time, the cooking loss rate of the noodles is 4-5%.
[0013] As a further improvement of the present invention, after the noodles are steamed within the optimal cooking time, the breaking force of the noodles is 70 to 75 g.
[0014] As a further improvement of the present invention, after the noodles are steamed within the optimal steaming time, the ductility of the noodles is 30 to 35 mm.
[0015] As a further improvement of the present invention, after the noodles are steamed within the optimal steaming time, the elongation of the noodles is 70-90%.
[0016] In a second aspect, the present invention provides a method for preparing noodles containing self-assembled nano-aggregates of tea polyphenols, the preparation steps comprising: S1. weighing raw materials according to the above-mentioned ratio; S2. mixing konjac gum and flour evenly to form a first mixture; S3. adding soda ash and salt to tea soup and fully dissolving them to form a first mixed liquid; S4. adding the first mixed liquid to the first mixture, kneading to prepare dough, and finally making noodles.
[0017] The present invention has the beneficial effects of producing noodles with an optimal cooking time, a low cooking loss rate, and excellent breaking strength, ductility, and elongation. Furthermore, the various raw materials ensure that the polyphenols in the yellowed green tea self-assemble and form stable nano-aggregates, thereby improving the taste of the green tea noodles without adding other nutrients. Furthermore, the green tea noodles retain the antioxidant properties of the yellowed green tea, further enhancing the nutritional value of the noodles. DETAILED DESCRIPTION
[0018] The present invention is further described in detail below based on implementation cases.
[0019] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention, rather than to represent all embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without creative work are within the scope of protection of the present invention.
[0020] In this embodiment, the flour used is produced from the high-gluten wheat flour of Wilmar Golden Dragon Fish Food Group Co., Ltd., and the yellow green tea used is the "Zhonghuang No. 1" yellow green tea, which comes from Sichuan Sanshan Tea Co., Ltd. The yellow green tea is bred from the naturally yellow variant single plant of the local group variety in Tiantai County through single plant selection-cutting propagation-variety comparison experiment-national regional trial and other procedures, and has passed the non-major crop variety registration in 2019.
[0021] Example 1:
[0022] This embodiment provides a method for preparing noodles containing tea polyphenol self-assembled nano-aggregates, and the preparation steps specifically include:
[0023] S1. according to the ratio, 50g tea soup, 0.3g soda ash, 1g salt, 4g konjac gum, 100g flour are weighed for standby use. Wherein, the tea-water ratio (tea leaves: water) of tea soup is 1:80. In the present embodiment, after taking 0.9g tea leaves and 72mL boiling water to mix and keep tea leaves soaking for 30min, it is filtered to obtain tea soup;
[0024] S2. The konjac gum and flour are mixed evenly to form a first mixture;
[0025] S3. Soda ash and salt are added to the tea soup and fully dissolved to form a first mixture;
[0026] S4. Add the first mixed liquid to the first mixture, knead the mixture to obtain dough, and finally produce noodles.
[0027] Preferably, the tea soup is divided into two portions according to the mass ratio of soda ash to salt, and soda ash and salt are added to each portion of the tea soup, respectively, before mixing. In this embodiment, the mass ratio of soda ash to salt is 3:10. Therefore, in S3, the tea soup is divided into a small portion of 12g and a large portion of 38g according to the mass ratio of soda ash to salt. Then, soda ash is added to the small portion of the tea soup, and salt is added to the large portion of the tea soup. After stirring to dissolve, the two portions of tea soup are then mixed together.
[0028] Preferably, the first mixed liquid is filtered using a filter membrane with a cut-off pore size of 0.22 μm to obtain concentrated tea polyphenol self-assembled nanoaggregates.
[0029] Example 2:
[0030] The difference between this embodiment and embodiment 1 is that, in this embodiment, the ratio adopted is: 50g tea soup, 0.4g soda ash, 1.5g salt, 2g konjac gum, and 100g flour.
[0031] Example 3:
[0032] The difference between this embodiment and embodiment 1 is that, in this embodiment, the ratio adopted is: 50g tea soup, 0.2g soda ash, 2g salt, 3g konjac gum, and 100g flour.
[0033] Example 4:
[0034] The difference between this embodiment and embodiment 1 is that, in this embodiment, the tea-to-water ratio (tea leaves: water) of the tea soup used is 1:60.
[0035] Example 5:
[0036] The difference between this embodiment and embodiment 1 is that, in this embodiment, the tea-to-water ratio (tea leaves: water) of the tea soup used is 1:40.
[0037] Comparative Example 1:
[0038] The difference between this comparative example and Example 1 is that in this comparative example, the amount of soda ash used is 0.6 g.
[0039] Comparative Example 2:
[0040] The difference between this comparative example and Example 1 is that in this comparative example, the amount of salt used is 3 g.
[0041] Comparative Example 3:
[0042] The difference between this comparative example and Example 1 is that, in this comparative example, the amount of konjac gum used is 6 g.
[0043] Comparative Example 4:
[0044] The difference between this comparative example and Example 1 is that in this comparative example, the amount of soda ash used is 0.6 g and the amount of salt used is 3 g.
[0045] Comparative Example 5:
[0046] The difference between this comparative example and Example 1 is that, in this comparative example, the amount of soda ash is 0.6 g, and the amount of konjac gum is 6 g.
[0047] Comparative Example 6:
[0048] The difference between this comparative example and Example 1 is that, in this comparative example, the amount of salt is 3 g, and the amount of konjac gum is 6 g.
[0049] Comparative Example 7:
[0050] The difference between this comparative example and Example 1 is that, in this comparative example, the amount of soda ash is 0.6 g, the amount of salt is 3 g, and the amount of konjac gum is 6 g.
[0051] First mixed solution test:
[0052] When the polyphenols in the first mixed liquid undergo self-assembly, corresponding nano-aggregates will be produced. Therefore, in this detection process, the particle size, Zeta potential and polyphenol content are mainly measured to prove that the polyphenols in the first mixed liquid have self-assembled.
[0053] The zeta potential measurement steps mainly include: S1. Cleaning the measuring instrument and setting the detection temperature, which is set to room temperature, i.e., 23°C, in this test; S2. Taking 1 mL of the filtrate of the first mixed solution in Examples 1 to 5 and Comparative Examples 1 to 7 as a sample, adding it to the measuring instrument to measure the particle size and potential of each sample, and repeating the measurement three times for each sample.
[0054] The polyphenol content determination step mainly includes: using the Folin-phenol method to determine the polyphenol content of the first mixed solution under various conditions. The determination step includes: taking 1.0 mL each of the sample solution (extract), gallic acid working solution, and water (as a blank control) into a 10 mL stoppered graduated test tube, adding 5 mL of 10% Folin-phenol, shaking well, reacting for 3-5 minutes, adding 4.0 mL of 7.5% sodium carbonate solution, diluting to the scale, shaking well, and placing in the dark at room temperature for 1 hour. Finally, the absorbance value is measured at 750 nm using a spectrophotometer. Furthermore, it is necessary to prepare gallic acid (GA) standard solutions with concentration gradients of 10, 20, 30, 40, and 50 μg / mL, measure the absorbance, and draw a standard curve to assist in calculating the polyphenol content.
[0055] Table 1 Detection results of the first mixed solution
[0056] project Particle size (nm) Zeta potential measurement Polyphenol content (μg / kg) Example 1 300 -22 21 Example 2 310 -18 20 Example 3 320 -17 22 Example 4 280 -25 23 Example 5 250 -30 24 Comparative Example 1 600 -10 19 Comparative Example 2 800 -8 19 Comparative Example 3 500 -17 19 Comparative Example 4 1100 -4 18 Comparative Example 5 650 -8 19 Comparative Example 6 860 -6 19 Comparative Example 7 1200 -3 17
[0057] In the test results, in each group of Examples 1 to 5 and Comparative Examples 1 to 7, the particle size of the first mixed liquid reached above 1 nm while maintaining the polyphenol content at 15 μg / kg, and the first mixed liquid changed from a solution to a colloidal state, indicating that compared with the free polyphenols, the polyphenols in the first mixed liquid in each group underwent self-assembly and existed in the form of larger-sized nanoaggregates.
[0058] Meanwhile, the zeta potential measurements in Examples 1-5 remained below -20, indicating that the nanoaggregates in the first mixed solutions of Examples 1-5 were more stable and less likely to decompose or aggregate into larger structures. Therefore, the inventors speculate that the noodles prepared in Examples 1-5 fully utilize the more stable nanoaggregates generated by the polyphenol self-assembly phenomenon to preserve the polyphenols, resulting in higher nutritional value.
[0059] Noodles related testing:
[0060] First of all, without considering the taste and nutritional value, the noodles need to have a normal optimal steaming time, and after being steamed using the corresponding optimal steaming time, the noodles should have an appropriate water absorption rate and as little cooking loss rate as possible. Therefore, it is necessary to first test the optimal steaming time, water absorption rate and cooking loss rate.
[0061] The experimental steps for determining the optimal steaming time are as follows: 15 green tea noodles were placed in 500 mL of boiling water for 3 minutes. After boiling, one noodle was removed every 15 seconds and placed between two white plates. The noodles were then pressed firmly to observe whether a white core was present. The time when the white core disappeared was the optimal steaming time. This experiment was repeated 3 times.
[0062] The experimental steps for cooking loss rate and water absorption rate are as follows: accurately weigh a certain mass of green tea noodles (recorded as m1) and put it into 500mL boiling water. After cooking for the optimal cooking time, take it out and put it into cold water to cool for 10s. After taking it out, quickly wipe the moisture on the surface of the noodles and weigh it. The mass of the noodles at this time is recorded as m2. After cooling the water for cooking the noodles, transfer all of it to a 500mL volumetric flask and take 100mL and put it into a constant weight beaker (record the mass of the beaker as m0) and put it into an oven to dry to constant weight. The mass after drying is recorded as m3. Finally, the water absorption rate and cooking loss rate are calculated using the following formula.
[0063]
[0064] Secondly, the noodles need to have a normal taste, among which factors such as smell, taste, softness and hardness are relatively subjective. Therefore, after the noodles are steamed for the optimal cooking time, multiple evaluators are selected to taste them and conduct sensory scoring, and finally the corresponding results are statistically analyzed; at the same time, objective tests on the breaking force, ductility and elongation of the noodles are used as auxiliary.
[0065] The sensory evaluation of dried noodles was conducted using a nine-point scale. The total score of the six characteristics was used for the final statistics. The evaluation criteria for each characteristic are shown in Table 2:
[0066] Table 2 Sensory evaluation standards
[0067]
[0068] The breaking force, ductility, and elongation of noodles are tested as follows: green tea noodles are placed in 500 mL of boiling water and cooked for the optimal cooking time. The noodles are then removed from the boiling water and cooled in cold water for 10 seconds. The surface moisture of the noodles is then wiped dry with filter paper. The noodles are then inspected using a texture analyzer with a pre-test speed of 2.00 mm / s, a test speed of 2.00 mm / s, a post-test speed of 10 mm / s, a trigger force of 5 g, and a test distance of 100 mm. The breaking force, ductility, and elongation data are then read from the texture analyzer.
[0069] Finally, the nutritional value of the noodles was evaluated, and relevant indicators were tested after the noodles were stored in a cool place for 3 days, mainly including the determination of polyphenol content and antioxidant activity in the noodles.
[0070] The steps for determining the polyphenol content mainly include: polyphenol extraction and polyphenol content determination.
[0071] The experimental steps for polyphenol extraction are as follows: green tea noodles are dried, crushed, and passed through an 80-mesh sieve. 0.2 g of 80-mesh green tea noodle sample powder is placed in a 10 mL centrifuge tube, 5 mL of 70% methanol is added, and the mixture is shaken with a vortex machine and placed in a 70°C water bath for 10 minutes. After cooling, the mixture is placed in a centrifuge and centrifuged at 3600 rpm for 10 minutes. The supernatant is collected and the extraction is repeated twice. The combined extracts are dilute to 10 mL and shaken to obtain the sample solution.
[0072] The experimental steps for determining polyphenol content are as follows: 1.0 mL each of the sample solution (extract), gallic acid working solution, and water (for a blank control) are placed in a 10 mL stoppered graduated test tube. 5 mL of 10% forin phenol is added, shaken, and allowed to react for 3-5 minutes. 4.0 mL of 7.5% sodium carbonate solution is added, brought to the mark, shaken, and allowed to stand at room temperature in the dark for 1 hour. The absorbance is measured at 750 nm using a spectrophotometer. A gallic acid (GA) standard solution with a concentration gradient of 10, 20, 30, 40, and 50 μg / mL is prepared, the absorbance is measured, and a standard curve is plotted.
[0073] Antioxidant activity assays include DPPH free radical scavenging ability assay, ABTS free radical scavenging ability assay, and reducing power assay:
[0074] The sample solution was prepared using the above-mentioned polyphenol extraction method.
[0075] The experimental steps for determining the ability to scavenge DPPH free radicals include: dissolving DPPH in anhydrous ethanol to prepare a 0.14mmol / L standard solution, then further diluting the DPPH solution with water until its absorbance is stable within the range of 0.700±0.002 at a specific wavelength of 517nm, taking 0.40mL and 4.00mL of the sample extract and 0.14mol / L DPPH solution respectively, and mixing them. At the same time, in order to establish an experimental control, an equal volume of anhydrous ethanol is used to replace the sample as a blank control, and an equal volume of anhydrous ethanol is used to replace the DPPH solution as an experimental control. After being placed in a dark place at room temperature for 20 minutes, the absorbance of the reaction solution is measured at a wavelength of 517nm, and the DPPH free radical scavenging rate is calculated according to the formula:
[0076]
[0077] A i represents the absorbance of the experimental group; A represents the absorbance of the control group; A0 represents the absorbance of the blank group.
[0078] The experimental steps for determining the ability to scavenge ABTS free radicals include: mixing 7 mmol / L ABTS and 2.45 mmol / L potassium persulfate solution and placing it in the dark at room temperature overnight to prepare an ABTS stock solution. The prepared ABTS stock solution is diluted with water until the absorbance at 734 nm reaches 0.70±0.02. The sample extract is diluted 10-fold, and 0.10 mL and 1.50 mL of the sample dilution and ABTS working solution are mixed respectively. At the same time, in order to establish experimental controls, an equal volume of distilled water is used to replace the sample dilution as a blank control, and an equal volume of distilled water is used to replace the ABTS working solution as an experimental control. The solution is placed in the dark at room temperature for 1 hour. The absorbance of the reaction solution is measured at a wavelength of 734 nm, and the ABTS free radical scavenging rate is calculated according to the formula:
[0079]
[0080] In the above formula, A i represents the absorbance of the experimental group; A represents the absorbance of the control group; A0 represents the absorbance of the blank group.
[0081] The experimental steps for determining reducing power include: taking 2.00 mL of green tea noodle extract, adding 2.50 mL of 0.20 mol / L phosphate buffer (pH = 6.6) and 2.50 mL of 10 g / L potassium ferricyanide solution in sequence, mixing, and reacting in a 50°C water bath for 30 minutes, then adding 2.5 mL of 100 g / L trichloroacetic acid, centrifuging at 3000 r / min, taking 2.50 mL of the supernatant and mixing it with 0.50 mL of 0.10% ferric chloride aqueous solution, reacting at room temperature for 10 minutes, and then measuring the absorbance at a wavelength of 700 nm (using distilled water as a blank). The greater the absorbance, the stronger the reducing power.
[0082] The relevant test results of the above-mentioned noodles are shown in Table 3:
[0083] Table 3 Test results of dried noodles
[0084]
[0085]
[0086] From the statistical results in the above table, it can be seen that, first, within the ratio range provided by the present invention, the optimal steaming time of the noodles in Examples 1 to 5 falls within the range of 200 to 300 seconds, and the water absorption rate obtained by steaming falls within the range of 125 to 150%, and the cooking loss rate of the noodles falls within the range of 4 to 5%, which is similar to the relevant situation of common commercially available noodles and can have basic noodle characteristics.
[0087] On this basis, the sensory evaluation scores of the noodles in Examples 1-5 were maintained between 80 and 90 points, with the taste score, in particular, remaining between 7 and 9. The test results in Table 1 indicate that the production process of the noodles does not destroy the nanoaggregates formed by the self-assembly of polyphenols. These nanoaggregates can mitigate the bitterness and astringency inherent in green tea, and were therefore recognized and accepted by the majority of panelists. Furthermore, the test results for breaking strength, ductility, and elongation indicate that the noodles possess an appropriate taste.
[0088] During the nutritional value testing process, the noodles needed to be stored before testing. This is because the nanoaggregates of tea polyphenols in noodles containing self-assembled nanoaggregates are not easily oxidized, and thus retain a large amount of polyphenols and corresponding nutritional value, such as antioxidant properties, even after long-term storage. Combining the test results in Tables 1 and 3, the noodles prepared using the more stable first mixed solution in Examples 1-5 can maintain better antioxidant properties and other functions even after long-term storage, verifying the inventors' hypothesis that the stable self-assembled nanoaggregates of tea polyphenols produced in the first mixed solution are retained in the noodles and play their corresponding role, thereby improving the nutritional value of the noodles.
[0089] The results of Comparative Examples 1-7 in Table 1 show that increasing the soda ash content and / or salt content destabilizes the polyphenol self-assembly phenomenon, potentially resulting in fewer nanoaggregates remaining during noodle production. The test results in Table 3 corroborate those in Table 1, demonstrating that the noodles prepared in these comparative examples, due to their low content of tea polyphenol self-assembled nanoaggregates, led to lower sensory scores. Furthermore, after long-term storage, the polyphenols present in the noodles oxidized, resulting in a decrease in polyphenol content and antioxidant activity.
[0090] As shown in the test results of Tables 1 and 3, the increase in konjac gum content significantly affects the basic capabilities of the noodles, such as the water absorption rate, especially the cooking loss rate. Among them, the increase in konjac gum content leads to an increase in the cooking time of the noodles, an increase in cooking loss, and a decrease in sensory score. First, because the macromolecular substances such as glucomannan contained in konjac gum can swell and absorb water, the excessive konjac gum will increase the water absorption rate of the noodles. Secondly, konjac gum has the function of adhering to flour particles and can reduce cooking loss by adhering to floating flour. This makes the cooking loss of the noodles less when the addition amount of konjac gum is appropriate; however, when the addition amount of konjac gum is too much, it will cause an increase in the cooking time of the noodles, but instead increase the cooking loss rate. Finally, on the one hand, konjac gum also contains reducing sugars, amino acids, oxidases, etc., which are prone to browning and cause the color of the noodles to darken, affecting the appearance of the noodles; on the other hand, the brittleness of konjac gum itself may also affect the mouthfeel of the noodles, and the two phases ultimately jointly caused a reduction in sensory score. To sum up, konjac glucomannan uses too much materials, makes that in comparative example 3, fine noodles are difficult to meet the requirement as fine noodles of basis on the contrary.Simultaneously in this case, konjac glucomannan also makes the breaking force, ductility, the elongation storage capacity of fine noodles be affected, and the overlong cooking time also has caused the nano-aggregate produced by polyphenol self-assembly to be destroyed etc., finally also causes the fine noodles nutritional value to be weakened.
[0091] In summary, the ratio provided by the present invention first ensures that polyphenol self-assembly occurs in the first mixed liquid, producing sufficient and stable nano-aggregates, and then ensures that the above-mentioned nano-aggregates are not destroyed in the subsequent noodle production process, thereby improving the taste and nutritional value of the final noodles.
[0092] Finally, it should be noted that the above implementation cases are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above implementation cases, ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the above implementation cases, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the implementation cases of the present invention.
Claims
1. A kind of noodles containing tea polyphenols self-assembled nano-aggregates, characterized in that: The ingredients required for preparing the noodles include, by weight: 85-110 parts of flour, 0.1-0.5 parts of soda ash, 1-2.5 parts of salt, 2-3.5 parts of konjac gum, 30-60 parts of tea; The tea soup is prepared by brewing yellow green tea and water, wherein the mass ratio of the yellow green tea to the water in the tea soup is 1:(40-80).
2. The dried noodles containing tea polyphenols self-assembled nano-aggregates according to claim 1, characterized in that: The components required for preparing the noodles preferably include, by weight: 90-110 parts of flour, 0.1-0.3 parts of soda ash, 1.5-2.5 parts of salt, 2.5-3.5 parts of konjac gum, 30-50 parts of tea; The tea soup is prepared by brewing yellow green tea and water, wherein the mass ratio of the yellow green tea to the water in the tea soup is 1:(60-80).
3. The dried noodles containing tea polyphenols self-assembled nano-aggregates according to claim 1, characterized in that: The optimal cooking time of the noodles is 200 to 300 seconds.
4. The dried noodles containing tea polyphenol self-assembled nano-aggregates according to claim 3, characterized in that: After the noodles are steamed within the optimal steaming time, the polyphenol content of the noodles is 20-25 mg / kg.
5. The dried noodles containing tea polyphenol self-assembled nano-aggregates according to claim 3, characterized in that: After the noodles are steamed within the optimal steaming time, the water absorption rate of the noodles is 120-150%.
6. The dried noodles containing tea polyphenol self-assembled nano-aggregates according to claim 3, characterized in that: After the noodles are steamed within the optimal steaming time, the cooking loss rate of the noodles is 4-5%.
7. The dried noodles containing tea polyphenols self-assembled nano-aggregates according to claim 3, characterized in that: After the noodles are steamed within the optimal steaming time, the breaking force of the noodles is 70 to 75 g.
8. The dried noodles containing tea polyphenols self-assembled nano-aggregates according to claim 3, characterized in that: After the noodles are steamed within the optimal steaming time, the ductility of the noodles is 30 to 35 mm.
9. The dried noodles containing tea polyphenols self-assembled nano-aggregates according to claim 3, characterized in that: After the noodles are steamed within the optimal steaming time, the elongation of the noodles is 70-90%.
10. A method for preparing noodles containing tea polyphenol self-assembled nano-aggregates, characterized in that: The dried noodles are prepared according to the combination ratio described in any one of claims 1 to 2, and the preparation steps include: S1. Weigh the raw materials according to the ratio; S2. The konjac gum and flour are mixed evenly to form a first mixture; S3. Add soda ash and salt to the tea to fully dissolve to form a first mixture; S4. adding the first mixed liquid to the first mixture, kneading to prepare dough, and finally making noodles.
Citation Information
Patent Citations
Green tea fine dried noodles
CN108936281A